Copper-catalyzed ring expansion of 2-aminobenzothiazoles with alkynyl carboxylic acids to 1, 4-benzothiazines1. Issue 10 (14th March 2015) - Qiu, Jing-Wen; Hu, Bo-Lun; Zhang, Xing-Guo; Tang, Ri-Yuan; Zhong, Ping; Li, Jin-Heng
<x xml:space="preserve">Abstract</x> A novel copper-catalyzed ring expansion of 2-aminobenzothiazoles to 1, 4-benzothiazines is described.